Caracterização de azeites de oliva produzidos no Brasil e monitoramento da sua qualidade oxidativa durante o armazenamento - Berto, Bruna Maira (Universidade Federal de São Carlos, 2020)
Olive oil stands out among lipid sources due to its appreciated sensory characteristics and for the beneficial health effects linked to its consumption. However, during the storage and/or use of this oil, together with the formation of oxidation products, the loss of compounds with bioactive properties can occur. Therefore, the objective of this work is to characterize olive oils of national origin and to monitor their oxidative degradation during storage. The experimental part of the work was divided into three stages. The first consisted of characterizing two olive oil samples produced in Brazil (AO SP and AO RS) in terms of identity and quality parameters. After characterization, these samples were subjected to oxidation under usual storage conditions (room temperature) for 6 months. Samples were collected at different time intervals and analyzed for oxidative and quality parameters. In the last stage, a shelf-life study of one of the olive oil samples was conducted. Results allowed the identification of the majority and minority components present in the two samples of national olive oil evaluated in the present work. The main differences observed were that the AO SP sample had a higher oleic acid content, but lower in palmitic acid than the AO RS sample. Regarding the quality parameters, both national oils met the specifications of national legislation. From the oxidation procedure at room temperature, it was possible to observe that both commercial olive oils deteriorated rapidly, mainly due to the high formation of hydroperoxides. Finally, changes in oxidative and quality parameters were lower in the shelf-life study compared to oxidation conducted with exposure to air and light.
Characterization of olive oils produced in Brazil and monitoring its oxidative quality during storage
Keywords: Olea europaea L.; Parâmetros de identidade e qualidade; Estabilidade oxidativa; Índice de peróxidos; Identity and quality parameters; Oxidative stability; Peroxide value; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS